2021
DOI: 10.1002/pbc.29046
|View full text |Cite
|
Sign up to set email alerts
|

Unsatisfactory quality of E. coli asparaginase biogenerics in India: Implications for clinical outcomes in acute lymphoblastic leukaemia

Abstract: Background The biotherapeutic asparaginase is a cornerstone of therapy in acute lymphoblastic leukaemia (ALL). With limited access to the original native Escherichia coli‐derived asparaginase (EcASNase), a variety of EcASNase biogenerics are used in low‐middle‐income countries (LMICs). The variable quality of these biogenerics potentially influences clinical outcomes. Procedure Seven biogeneric EcASNases (P1–P7) marketed widely in India were evaluated, with P2 as an exemplar for in vivo monitoring. Therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 27 publications
3
19
0
Order By: Relevance
“…Many of these treatments are possible in India due to the availability of generics, and biosimilar preparations of drugs like L‐asparaginase (L‐ASAP) and rituximab. However, challenges remain 30,31 …”
Section: The Perspective From India (Vs Radhakrishnan and M Chandy)mentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these treatments are possible in India due to the availability of generics, and biosimilar preparations of drugs like L‐asparaginase (L‐ASAP) and rituximab. However, challenges remain 30,31 …”
Section: The Perspective From India (Vs Radhakrishnan and M Chandy)mentioning
confidence: 99%
“…However, challenges remain. 30,31 Our institution is a not-for-profit trust-based comprehensive cancer centre located in eastern India, and we are a regional referral institution. Referral pathways for cancer care in most of India are a work-in-progress, and are currently based on geographical access, payment patterns, and treatment experience and reputation of the centres.…”
Section: Q1 Diagnosismentioning
confidence: 99%
“…ASP biogenerics have been also used to face occasional shortages occurring for the original product in countries other than LMIC. 6,7 However, some recent reports have shown relevant pharmacological differences between these products and the reference products. As an example, Zenatti et al have recently reported insufficient SAA levels in a cohort of patients treated with a biogeneric ASP, produced by a Chinese company and marketed in Brazil, reportedly because of a high protein contamination of the product.…”
Section: Introductionmentioning
confidence: 99%
“…8 Similar evidence has been reported by Sidhu et al and Sankaran et al when describing drug activity and biological features of different ASP biogenerics, manufactured in India, reporting inadequacy of those products in terms of protein's purity and identity, chemical quality of the formulation, and activity levels. 6,7 In this report, we describe the pharmacological and clinical effects associated with the use of a PEG-ASP biogeneric product, manufactured in India and administered in a limited cohort of patients during the induction phase of an AIEOP-BFM ALL backbone-based protocol.…”
Section: Introductionmentioning
confidence: 99%
“…3 In the present study, Sidhu et al showed that none of the seven biogeneric formulations of native asparaginase marketed in India met the minimum manufacturing quality standards required for these products. 4 In a similar manner, Sankaran et al analyzed nine generic formulations of L-asparaginase. They observed that none of the nine Indian generic formulations tested were able to consistently achieve a threshold of 100 IU/L.…”
mentioning
confidence: 99%